MODEL PEMBELAJARAN UNTUK MENINGKATKAN LITERASI MEMBACA SISWA MI/SD: STUDI LITERATUR - Hardhika Wahyu Dewani (Hijri, 2025)
Reading literacy is a 21st-century competency that elementary school students must possess. However, reading literacy in Indonesia remains low. Effective learning models are essential for teachers to improve these skills. This study aims to identify learning models that can be implemented to improve reading literacy at the elementary school level. The study employed a qualitative approach with a literature review. This literature review is based on research findings from the past 10 years found on Google Scholar. The results indicate that learning models exist to improve reading literacy in Madrasah Ibtidaiyah (MI) or elementary school students